An Analysis of the Eleventh Grade Students’ Scanning Ability in Reading Advertisement at SMA Pembangunan Laboratorium UNP - Deby Oktaviani Rusdi; Yetti Zainil (Journal of English Language Teaching, 2019)
This research aimed to know the students’ scanning ability in reading advertisement.  This research is descriptive quantitative research. The population in this research is the eleventh grade students at SMA Pembangunan Laboratorium UNP. The sample was taken by using simple random sampling. There is 33 students that become the sample of the research. In this research, the data were collected through the reading test. Students were asked to answer all questions as quick as they can. The data were scored in general and every part of the test to check the quality of the students’ scanning ability in reading advertisement text.  Based on the findings and discussion about the students’ ability in reading advertisement, as a whole from all indicators tested found that three students who got category excelent, five students who got category good, eight students who got category satisfactory, and seventeen students who got category poor. So based on the results of the research shows that the eleventh grade students in SMA Pembangunan Laboratorium UNP was quite good in scanning ability in reading advertisement text.